2019
DOI: 10.3390/agriculture9090202
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cosmic-Ray Neutron Sensor for Soil Moisture Estimation over Large Areas

Abstract: A correct soil moisture estimation is a fundamental prerequisite for many applications: agriculture, meteorological forecast, flood and drought prediction, and, in general, water accounting and management. Traditional methods typically provide point-like measurements, but suffer from soil heterogeneity, which can produce significant misinterpretation of the hydrological scenarios. In the last decade, cosmic-ray neutron sensing (CRNS) has emerged as a promising approach for the detection of soil moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…flood modelling applications) when near-surface storage plays a dominant role in runoff generation. Additionally, landscape-average estimates of SWCCRNS can be extremely valuable for agricultural management applications that reply on soil moisture status (Franz et al, 2016;Stevanato et al, 2019). These and other applications, such as flood warning systems, would therefore benefit significantly from the better internal representation of SWC that CRNS data can bring to rainfall-runoff models.…”
Section: How Can Shallow Soil Moisture Information Be Used To Help Better Characterize Catchment Storage In Rainfall-runoff Models and Whmentioning
confidence: 99%
“…flood modelling applications) when near-surface storage plays a dominant role in runoff generation. Additionally, landscape-average estimates of SWCCRNS can be extremely valuable for agricultural management applications that reply on soil moisture status (Franz et al, 2016;Stevanato et al, 2019). These and other applications, such as flood warning systems, would therefore benefit significantly from the better internal representation of SWC that CRNS data can bring to rainfall-runoff models.…”
Section: How Can Shallow Soil Moisture Information Be Used To Help Better Characterize Catchment Storage In Rainfall-runoff Models and Whmentioning
confidence: 99%
“…Their study revealed the similarity of the CRNPs to Bonner Spheres (Bramblett et al, 1960;Hertel and Davidson, 1985;Mares et al, 1991;Mares and Schraube, 1994) in terms of energy sensitivity. Beyond the standard probes recent developments also aim to introduce scintillation-based instruments (Stevanato et al, 2019). Besides the achievable count rate, the main difference between the two concepts lies in the detector energy response function and the background suppression.…”
Section: Introductionmentioning
confidence: 99%
“…iaea.org/publications/11097/cosmic-rayneutron-sensing-use-calibration-andvalidation-for-soil-moisture-estimation). Another interesting paper on the subject is Stevanato et al (2019).…”
Section: Webinars Worth Watchingmentioning
confidence: 99%